Lead from the Outside How to Build Your Future and Make Real Change - Stacey Abrams, read by the Author (New York Macmillan., 2018)
"Abrams's own grit, coupled with her descriptions of much stumbling and self-doubt, will make [Lead from the Outside] touch you in a way few books by politicians can." (The New York Times)
Keywords: Leadership